Misrepair of DNA double-strand breaks in patient with unidentified chromosomal fragility syndrome and family history of radiosensitivity. (January 2014) - Alsbeih, Ghazi; Brock, Williams; Story, Michael
Abstract Purpose: To test the hypothesis that differences in DNA double-strand breaks (DSB) repair fidelity underlies differences in radiosensitivity. Materials and methods: A primary fibroblast culture (C42) derived from a pediatric cancer patient treated with reduced radiation doses consequent to a family history of radiosensitivity reminiscent of chromosomal fragility syndrome, was compared to a normal control (C29). DNA DSB rejoining and repair fidelity were studied by Southern blotting and hybridization to specific fragments: Alu repetitive sequence representing the overall DSB rejoining capacity in the genome and a 3.2 Mbp NotI restriction fragment on chromosome 21 for DSB repair fidelity. Results: Although both assays showed statistically significant difference (p ≤ 0.05) between the two cell strains in residual misrepaired (un-or mis-rejoined) DSB (24 h after 30 or 80 Gy), the residual damage was lower in the Alu enriched genome assay compared to NotI assay (0.01–0.07 and 0.10–0.37, respectively). Conclusions: These results suggest that, in comparison to classic DSB repair experiment, an assay of measuring DNA DSB repair fidelity can provide better resolution and a more accurate estimate of misrepair of radiation-induced DNA damage, which underlies genomic instability and increased radiosensitivity.